Neuroinflammation and neurotoxicity contribute to neuroprogression in neurological and psychiatric disorders. (29th May 2018) - Halaris, Angelos
The immune system and inflammatory processes contribute to brain-related pathologies in most, if not all, neurological and psychiatric disorders. Stress is a key factor in inducing immune system dysregulation in conjunction with genetic, epigenetic and environmental factors. Activation of the immune response can alter neurotransmission leading, among others, to serotonin deficiency, and increased production of neurotoxic substances contributing to disease progression. The concept of neuroprogression is gaining acceptance among clinicians and researches as it seeks to explain the mechanism(s) responsible for disease chronicity, recurrence and treatment resistance. Therefore, measurement of neuroinflammatory biomarkers along with assessment of neurotoxic metabolites, oxidative stress and neuroplasticity impairment, will ultimately be useful tools to predict and possibly prevent the development and progression of neuropsychiatric disorders as well as to identify the most efficacious treatments.